Modification of Grass Chopper Blade from Leaf Spring with Coconut Shell Charcoal Addition by Carburizing Treatment - Febritasari, Rosadila; Sutrisno, Tito Arif; Jikwa, Herlan Hafiidh; Berta, Dhea Rosali; Artayasa, I Made Pande; Nahak, Bernadino Arsinyo; Yordan H. P.I, Yohanes (Program Studi Teknik Mesin Universitas Pamulang, 2024)
A grass chopper is a machine used to chop grass and soft stems. In the grass chopping process, a sharp blade is required. The current problem is the blade get wear due to repeated sharpening of the blade, resulting in a non-uniform texture of chopped grass and often found some large grass sizes. Therefore, this research focuses on blade material engineering. This research was conducted by carburizing at 700°C for 60 minutes and adding carbon from coconut shell charcoal followed by quenching using water cooling media. The blade was made from a leaf spring made of JIS-SUP 9 steel. The results showed 106% of enhancement in carbon composition after the blade was treated by carburizing. This carbon composition enhancement affects the performance of the blade, namely higher hardness as shown by a 175% increase in hardness value and a 96.4% lower wear rate than the untreated blade.